Challenges of Collaborative Governance: An Organizational Discourse Study of Public Managers' Struggles with Collaboration across the Daycare Area - Mie Plotnikof (Copenhagen Business School (CBS), 2015)
This doctoral study explores problematics of managing and organizing collaborative governance from an organizational discourse perspective. Collaborative governance is a public management practice developing currently with the aim of engaging stakeholders to address and co-create potential solutions to complex public problems, such as policy and service innovation. This is seen as a potential shift between new public management (NPM) and new public governance (NPG) discourses in the governance literature. Pursuing collaborative governance in practice is not taken to be an easy task, as it involves changes from hierarchical organizing towards interorganizational collaboration in networks and partnerships. The literature therefore discusses both the potentials and problems, and conceptualizes their issues in organizational models of design and implementation issues, and new managerial roles. These issues are approached as managerial challenges and unfolded in terms of paradoxes, socially dynamic tensions and power relations – especially by one stream of studies. They stress the need to understand challenges of collaborative governance practice by approaching the emerging social interactions and power relations; however, the theorization of communication and discursive aspects to do so is underdeveloped.
hdl:10398/9185
Keywords: 650